The Limits of Sustainable Palm Oil: Agrarian Culture and The Politics of Good Agriculture Practice Implementation in North Aceh - Ade Ikhsan Kamil; M. Nazaruddin; Subhani; Mujiburrahman Mujiburrahman; Khairunnisa Hasibuan; Septriani Septriani (Universitas Andalas, 2026)
This study examines the implementation of Good Agricultural Practices (GAP) within the framework of Roundtable Suistanable Palm Oil (RSPO) and Indonesian Sustainable Palm Oil (ISPO) certification, highlighting the tension between global standards and local agrarian realities. While GAP is promoted as a technical tool to enhance productivity and sustainability, its application often follows a top-down approach that overlooks local socio-cultural contexts. Using a qualitative ethnographic method, this research uses North Aceh as a case study. Data were collected through field observations, in-depth interviews with smallholders, customary leaders, and local actors, as well as analysis of RSPO and ISPO policy documents. An anthropological perspective is employed to understand power relations, cultural meanings, and community responses to technocratic standards. Findings show that GAP implementation faces key challenges, including unclear land tenure, limited access to technology and training, and low trust toward government and plantation companies. GAP standards often conflict with customary systems and local knowledge, leading smallholders to perceive them as administrative and economic burdens. However, adaptive strategies such as agroforestry and locally grounded sustainable practices demonstrate farmers’ capacity to negotiate these demands. The study concludes that effective GAP implementation requires integrating local cultural values and strengthening the role of customary institutions as mediators between global standards and local practices.